Autoimmune Polyglandular Syndrome Type 2 Presentation with Alopecia Universalis, Hashimoto’s Disease, and Addison’s Disease - Sales-Morales KD; Torres-Neme N; Barrera-Villanueva V; Martínez-Carreón A (International Medical Case Reports Journal, 2025)
Karla Denisse Sales-Morales,1,* Nazhira Torres-Neme,2 Vladimir Barrera-Villanueva,3 Alejandro Martínez-Carreón1,* 1Department of Internal Medicine, High Specialty Regional Hospital, ISSSTE, Veracruz, Mexico; 2Department of Endocrinology, High Specialty Regional Hospital, ISSSTE, Veracruz, Mexico; 3Department of Nephrology, High Specialty Medical Unit, Specialty Hospital No. 14, “Adolfo Ruiz Cortines” National Medical Center, Mexican Social Security Institute (IMSS), Veracruz, Mexico*These authors contributed equally to this workCorrespondence: Alejandro Martínez-Carreón, Email alejandromtc23@hotmail.comAbstract: Autoimmune polyglandular syndrome type 2 (APS2) is characterized by the coexistence of primary adrenal insufficiency with autoimmune thyroid disease and/or type 1 diabetes. APS2 frequently includes conditions affecting non-endocrine organs, such as alopecia, vitiligo, celiac disease, and autoimmune gastritis associated with vitamin B12 deficiency. We report the case of a 30-year-old male with a history of Hashimoto’s disease and alopecia universalis, who presented with diarrhea, anorexia, hypoglycemia, and abdominal pain. Physical examination revealed orthostatic hypotension, a non-tender abdomen, and generalized hair loss. Initial laboratory workup showed hyponatremia and hyperkalemia. Further testing, including serum cortisol, ACTH, aldosterone, and 21-hydroxylase antibodies, confirmed the diagnosis of Addison’s disease. The patient was treated with prednisone and fludrocortisone. Only two previous cases of APS2 associated with alopecia universalis have been reported: one with concurrent Crohn’s disease and another with hypoparathyroidism. This case highlights the importance of recognizing non-endocrine manifestations in patients with autoimmune endocrinopathies to facilitate earlier diagnosis and management.Keywords: autoimmune polyglandular syndrome type 2, alopecia universalis, Addison’s disease, adrenal crisis